Natural Resources and Small Island Economies: Mauritius and Trinidad and Tobago. Issue 2 (1st February 2017) - Auty, R. M.
A bstract: Historically, small economies, especially resource-rich ones, underperformed on average relative to their larger counterparts. Small island economies appear still more disadvantaged due to remoteness from both markets and agglomeration economies. Yet a comparison of two small island economies with similar initial conditions other than their mineral endowment suggests that policy outweighs size, isolation and resource endowment in determining economic performance. Resource-poor Mauritius adopted an unfashionable policy of export manufacturing that systematically eliminated surplus labour, which drove economic diversification that sustained rapid GDP growth and political maturation. Like most resource-rich economies, Trinidad and Tobago pursued policies that absorbed rent too rapidly, which impeded diversification and created an illusory prosperity vulnerable to collapse.